Optimalisasi Digital Marketing sebagai Strategi Pemasaran UMKM Pasca Pandemi Covid-19 di Desa Parungsueah Kabupaten Sukabumi - Tarissa Nur Noviana; Dadan Rahmat; Prieyayi Nuryusuf (Universitas Kristen Satya Wacana Salatiga, 2022)
The COVID-19 pandemic has had a bad impact on Indonesia's economy, particularly in Desa Parungseah, Kabupaten Sukabumi. Because of how difficult it is to market a product during the COVID-19 pandemic, many UMKM have seen a decrease in income, even to the point of going out of business. The object of this program is businessman UMKM from Desa Parungseah. The KKN-T program was held on Desa Parungseah, Kabupaten Sukabumi. The implementation method for this program is making a UMKM seminar about